Synthesis of Bifunctional Furano-Allocolchicinoids - Gracheva, Iuliia A.; Svirshchevskaya, Elena V.; Zaburdaeva, Elena A.; Fedorov, Alexey Yu. (Synthesis, 2017)
An efficient seven-step semisynthetic approach towards non-racemic bifunctional furano-allocolchicinoids, starting from naturally occurring colchicine is presented. The Pd-catalyzed domino Sonogashira coupling/5-endo-dig cyclization was employed as the key step. The prepared compounds exhibited substantial cytotoxicity against T3M4, MiaPaCa-2, Colo-357, and PANC-1 cell lines. The presence of two functionalities with different reactivity (hydroxyl and amino groups) in the target molecules allows for an easy conjugation of furano-allocolchicinoids with drug delivery carriers, and opens promising opportunities for their further exploitation in the search of therapeutics.
Keywords: antitumor agents; tubulin; colchicine; allocolchicinoids; heterocycles